Adipocytokine correlations with thyroid function and autoimmunity in euthyroid sardinians. (November 2018) - Delitala, Alessandro P.; Steri, Maristella; Fiorillo, Edoardo; Marongiu, Michele; Lakatta, Edward G.; Schlessinger, David; Cucca, Francesco
Highlights: Leptin is positvely associated with TSH levels. Leptin and TSH might interact in the context of energy homeostasis. Adiponectin is associated with markers of thyroid autoimmunity. Abstract: Objective: Cytokines release by adipocytes could interact with TSH secretion. We evaluated the relationship between adipocytokines and TSH. We further tested for association of cytokines and thyroid autoimmunity. Methods: We conducted a cross-sectional study in a community-based sample including 5385 individuals (2964 female) with TSH within the reference range. Subjects who reported taking thyroid medications or drugs that alter thyroid function were excluded. TSH, FT4, adiponectin, leptin, antibody against thyroperoxidase and against thyroglobulin were measured. Linear and logistic regression models were used to test for association. Results: Females had higher adiponectin and leptin level and increased frequency of thyroid antibodies. In multiple regression analysis TSH was directly associated with leptin (β = 0.003, p = 0.001) and the presence of circulating antibody against thyroperoxidase (β = 0.315, p < 0.001), but negatively associated with age (β = −0.012, p < 0.001) and FT4 (β = −0.359, p < 0.001). Adiponectin, the presence of antibody against thyroglobulin and smoking habit were not associated with TSH levels (p = 0.223, p = 0.174 and p = 0.788, respectively). Logistic regression analysis revealed that higher adiponectin levels were associated with thyroid autoimmunity. Conclusions: Leptin is positively associated with TSH levels in euthyroid individuals, suggesting an effect of the adipokine on TSH secretion. Our results support the hypothesis that the leptin and pituitary-thyroid axis might interact in the context of energy homeostasis. The effect of adiponectin on thyroid autoimmunity will require more studies.